answersLogoWhite

0


Best Answer

3s + 4t + 2s + 5s + 6t

Group all of the like 's' terms & 't' terms together:

(3s+2s+5s) + (4t + 6t)

10s + 10t or 10(s+t)

User Avatar

Wiki User

โˆ™ 2011-11-17 17:11:55
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is 3s plus 4t plus 2s plus 5s plus 6t equals?
Write your answer...
Submit
Related questions

What is 4t plus 3s plus 2p equals c?

math


What is 3t plus 2s plus t plus 5s?

7s + 4t


What is the answer to 4t plus 5 equals 37?

If 4t + 5 = 37, then t = 8.


What is the answer to 9t equals 4t plus 120?

9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer


If 4t plus 10 equals 18 what does t equal?

2


What is 9 equals 5 plus 4t?

It is an equation and the value of t is 1


What does t mean in the equation...42 equals 18t plus 4t plus 5?

NEVERMIND!


T plus 3-2t equals 4t plus 1?

T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed. t+(3-2t)=4t+1 3-t=4t+1 2-t=4t 2=5t last step is yours


Four times t minus eight plus twenty equals 5?

t in this problem equals -3. 4t- 8+ 25= 5 -25 -25 4t- 8= -20 +8 +8 4t= -12 /4 /4 t= -3


Solve 4t-1 equals t plus 2?

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1


What is 4t plus 13t plus 2?

4t + 13t + 2 = 17t + 2


What is 4t equals 24?

4t = 24 Therefore t = 24/4 t = 6


How would you solve for t t plus 10-4t equals -11?

t + 10 - 4t = -11 Subtract 10 from each side: t - 4t = -21 ie -3t = -21 t = -21/-3 t = 7.


What is the answer to 4t-3 equals 19?

4t - 3 = 19 4t = 19 +3 = 22 t = 22/4 t = 5.5


How many T equals 8000lb?

4T


What is p equals 4t plus 2?

You don't have enough information to solve this. You need to know what P is, or what T is, otherwise you can't get an answer.


What is 2t plus 7 plus 2t?

4t +7


Which equation is equivalent to 4t equals 20?

-2t = -10


4T equals how many pounds?

8,000 lbs


How do you solve this equation -4t plus 5t-8 plus 4 equals 6t-4?

-4t+5t-8+4=6t-4 eqn soln t=0 transpose variable terms on one side & constant terms on the other side of equality


What is 4t-6 when t equals -6?

4t - 6 = 4*(-6) -6 = -24 -6 = -30


10t equals 6t plus 24?

10t=6t+24 -6 -6 4t=24 4 4 1=6 t=6


How many 4T 625 lb equals to how many pounds?

8625lb


How do you factor T2 plus 4T?

T(t + 4)


Tcubed plus 4t squared plus 4t LCM?

That's one term. You need at last two to find an LCM. That factors to t(t + 2)(t + 2)